Lift characteristic analysis of Coanda jet on curved surfaces with varying inclination angles - Md Shafie, Muhammad Alimin (2022)
With the applications of small unmanned aerial vehicles (UAVs) getting much more diverse, the need for a system that is capable of high lift force augmentation is important for longer flight endurance while possessing the versatility to perform diverse flight missions. Coanda UAV is one of the options. To address the said need, the current study explored the influence of the curved surface inclination angle on the lift augmentation performance and the Coanda jet flow behavior since the potential effects of curved surface inclination angle to lift performance are yet to be fully studied. In this study, both experimental and numerical computation approaches were employed for the analysis involving two curved surfaces with the curvature ratios of 1 and 2 with a jet velocity of 10 m/s to 30 m/s while the surface inclination angles varying in the range of 0° to 40° were analyzed through computational analysis. The experimentation used the static pressure measurement method measured through 13 static pressure tap holes to plot the static pressure distribution along the test models whereas the numerical computation utilized Computational Fluid Dynamic (CFD) method using the k-ω SST CC turbulence model to simulate the Coanda jet flow. Both analyses deal with the 2-dimensional (2D) Coanda jet flow. The experimental data gave an overview of the static pressure distribution along the curved surface on different surfaces with curvature and showed the total lift performance of curvature ratio 2 is 52% more than the curvature ratio 1. The result extracted from CFD analysis closely followed the experimental data with a percentage difference of 6%. Similar to the experiment data, the curvature ratio 2 produced 32% more lift force. The lift force generated under the effect of surface inclination angles, however, showed a fluctuating pattern and the highest generated lift force is obtained at 0° surface inclination angles valued at 5.23 N and 7.1 N for the curvature ratio 1 and 2, respectively. Nevertheless, the Coanda jet flow is capable to remain attached to the end of the surface at all surface inclination angles, and a slight increase of jet thickness of at least three times the initial jet thickness is observed at the edge of the curved surface in all inclination angles due to addition of mass flow from the entrained fluid. An increase in surface inclination angle resulted in a thicker jet though the change is minimal. On the whole, the current study offers an analysis result on the impact of surface inclination angle on lift performance and demonstrated that designing the Coanda UAV with a greater curvature ratio and assuming a 0° surface inclination angle results in the highest generated lift force.